Consequences of Team Job Demands: Role Ambiguity Climate, Affective Engagement, and Extra-Role Performance - Mañas, Miguel A.; Díaz-Fúnez, Pedro; Pecino, Vicente; López-Liria, Remedios; Padilla, David; Aguilar-Parra, José M. (Frontiers in Psychology, 2018)
In the absence of clearly established procedures in the workplace, employees will experience a negative affective state. This situation influences their well-being and their intention to behave in ways that benefit the organization beyond their job demands. This impact is more relevant on teamwork where members share the perception of ambiguity through emotional contagion (role ambiguity climate). In the framework of the job demands and resources model, the present study analyzes how high levels of the role ambiguity climate can have such an effect to reduce employee affective engagement. Over time it has been associated with negative results for the organization due to a lack of extra-role performance. The sample included 706 employees from a multinational company, who were divided into 11 work teams. In line with the formulated hypotheses, the results confirm the negative influence of the role ambiguity climate on extra-role performance, and the mediated effect of affective engagement in the relationship between the role ambiguity climate and extra-role performance. These findings indicate that the role ambiguity climate is related to the adequate or inadequate functioning of employees within a work context.